2011
DOI: 10.1186/1477-7819-9-166
|View full text |Cite
|
Sign up to set email alerts
|

Expression of circadian clock gene human Period2 (hPer2) in human colorectal carcinoma

Abstract: BackgroundRecent studies have shown that disruption of circadian rhythms is one of the tumor promoting factors which contribute to mammalian cancer development and progression, but very little is known about the molecular changes of circadian genes in colorectal carcinoma (CRC). Thus, in this study, changes in the expression of human Period2 (hPer2), one of the key circadian clock regulators, in CRC and its correlation with prognosis were investigated.MethodsImmunohistochemical (IHC) staining and real-time PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 33 publications
(39 reference statements)
5
35
0
Order By: Relevance
“…These experimental studies suggested that Period genes control the cell cycle and act as tumour suppressors. This is consistent with the findings in this review where Period is decreased in colorectal tumours . Decreased expression of Period genes has also been reported in other types of cancer such as breast cancer , endometrial carcinoma , non‐small‐cell lung cancer , acute myeloid leukaemia , gliomas and hepatocellular carcinoma .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These experimental studies suggested that Period genes control the cell cycle and act as tumour suppressors. This is consistent with the findings in this review where Period is decreased in colorectal tumours . Decreased expression of Period genes has also been reported in other types of cancer such as breast cancer , endometrial carcinoma , non‐small‐cell lung cancer , acute myeloid leukaemia , gliomas and hepatocellular carcinoma .…”
Section: Discussionsupporting
confidence: 92%
“…1). Characteristics of the 11 studies are given in Table 1 [27][28][29][30][31][32][33][34][35][36][37].…”
Section: Resultsmentioning
confidence: 99%
“…Bmal1, Npas2 and Clock have been indicated as important for VEGF-production during the night [33,34]. In agreement with these findings, Clock is often up-regulated and Period2 downregulated in human colorectal cancer and the levels of tumor Clock expression exhibit a tight positive correlation with tumor VEGF-levels and metastatic dissemination in patients [35,36].…”
Section: Role Of Circadian Clocks In Cancersupporting
confidence: 68%
“…From a molecular point of view, and in agreement with the findings from pre-clinical models, CLOCK was reported to be significantly up-regulated and Per2 was down-regulated in human colorectal cancer tumors compared to adjacent healthy tissue and the levels of CLOCK from different patients strongly correlated with the level of VEGF detected in their tumor biopsies as well as degree of metastatic dissemination of tumor cells and poor prognosis (91,92). In addition, other angiogenic factors have been found to oscillate in a circadian fashion, including bFGF, EGF and IGFBP in breast cancer patients, where peak plasma levels are generally found during the day and low levels in the night (93).…”
Section: The Role Of the Circadian Clock In Human Tumor Angiogenesissupporting
confidence: 64%